Drug Repurposing - Hypothesis, Molecular Aspects and Therapeutic Applications 2020
DOI: 10.5772/intechopen.92803
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repositioning for the Treatment of Glioma: Current State and Future Perspective

Abstract: Gliomas are the most common primary brain tumors. Among them, glioblastoma (GBM) possesses the most malignant phenotype. Despite the current standard therapy using an alkylating anticancer agent, temozolomide, most patients with GBM die within 2 years. Novel chemotherapeutic agents are urgently needed to improve the prognosis of GBM. One of the solutions, drug repositioning, which broadens the indications of existing drugs, has gained attention. Herein, we categorize candidate agents, which are newly identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 122 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…We also undertook an in vivo study by generating a xenograft mouse model of human GBM, and IHC staining of specimens reproduced these findings in the in vitro study. Interestingly, our results indicated that PE has a strong antitumor effect in GICs 16 . Additionally, we successfully generated differentiated GICs and compared the influence of PE on intracellular signaling between GICs and differentiated GICs.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…We also undertook an in vivo study by generating a xenograft mouse model of human GBM, and IHC staining of specimens reproduced these findings in the in vitro study. Interestingly, our results indicated that PE has a strong antitumor effect in GICs 16 . Additionally, we successfully generated differentiated GICs and compared the influence of PE on intracellular signaling between GICs and differentiated GICs.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, our results indicated that PE has a strong antitumor effect in GICs. 16 Additionally, we successfully generated differentiated GICs and compared the influence of PE on intracellular signaling between GICs and differentiated GICs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations